Nursing care of a critically ill child with perianal necrotizing fasciitis (1例肛周坏死性筋膜炎危重症患儿的护理) - GU Chanjuan (顾婵娟); JU Minjie (居敏洁); LIU Ji (刘季); YANG Xiaoya (杨晓亚); LU Lingling (陆凌玲) (Journal of International Translational Medicine Limited, 2024)
To summarize the nursing experience of a 4-month-old critical ill child with perianal necrotizing fasciitis complicated with severe sepsis, refractory septic shock and respiratory failure. The key points of nursing include: Timely assessment of wounds and wound conditions; Strengthening wound care and promote wound healing; Strengthening perianal and perineal nursing to prevent infection; ensuring the safety of the child and avoiding the pressure of the stoma and the wound; Attention should be paid to the use of sedative and analgesic drugs in children, and analgesic evaluation should be strengthened to reduce pain in children. After 24 days of careful care, the child's condition was stable. The wound had healed well, and the child had been transferred to the general ward for continued treatment. (本文总结1例肛周坏死性筋膜炎(NF)危重症患儿的护理经验。护理要点包括: 及时评估伤口和创面的情况, 调整伤口护理措施; 加强伤口护理, 促进伤口愈合; 加强肛周、会阴护理预防感染; 积极变换体位, 避免造口及创面受压; 科学使用儿童镇静镇痛药物, 加强镇痛评估, 减轻患儿疼痛。经过24 d的精心治疗和护理, 患儿病情稳定, 伤口愈合良好, 转往普通病房继续治疗。)